2021
DOI: 10.3390/children8090781
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Inherited Metabolic Disorders: One-Year Experience of a Referral Center

Abstract: Understanding the potential risks of patients with inherited metabolic disorder (IMD) exposed to the COVID-19 pandemic is an unmet need for those involved in their management. Here, we report on the incidence of COVID-19 in a cohort of patients with IMD treated at a children’s hospital and compare them with a matched control group. Among the total number of 272 patients actively followed at a referral center, 19 (7%) tested positive for SARS-CoV-2 between March 2020 and March 2021. Their median age was 16.2 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Studies on the impact and the outcome of COVID-19 infection in IMD patients are scarce. There are a few reports on the clinical impact of COVID-19 infection in IMD patients with different clinical responses ranging from mild to severe presentation ( Zubarioglu et al, 2021 ; Sibulo et al, 2021 ; Saad-Naguib et al, 2021 ; Kaur et al, 2021 ; Caciotti et al, 2020 ; Wongkittichote et al, 2020 ; Climent et al, 2020 ; Lampe et al, 2020 ; Tummolo et al, 2021 ; Tobór-Świętek et al, 2021 ). Due to the uniqueness of this group of patients and the lack of extensive literature reports, the management of COVID-19 infection has been challenging for many health care providers ( Lampe et al, 2020 ; Tobór-Świętek et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the impact and the outcome of COVID-19 infection in IMD patients are scarce. There are a few reports on the clinical impact of COVID-19 infection in IMD patients with different clinical responses ranging from mild to severe presentation ( Zubarioglu et al, 2021 ; Sibulo et al, 2021 ; Saad-Naguib et al, 2021 ; Kaur et al, 2021 ; Caciotti et al, 2020 ; Wongkittichote et al, 2020 ; Climent et al, 2020 ; Lampe et al, 2020 ; Tummolo et al, 2021 ; Tobór-Świętek et al, 2021 ). Due to the uniqueness of this group of patients and the lack of extensive literature reports, the management of COVID-19 infection has been challenging for many health care providers ( Lampe et al, 2020 ; Tobór-Świętek et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, patients with PKU are less subjected to such influences than most patients with IMD. Tummolo et al [ 22 ] reported a moderate influence of the COVID-19 pandemic on a relatively numerous cohort of IMD patients, which included children and young adults, but Chung et al established that patients with rare diseases had a 3.4 times higher OR of hospital death from COVID-19-related causes than the general population [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of COVID-19 infection in patients with MSUD have only been documented in two prior publications [ 6 , 7 ]. The first, an observational cohort study examining COVID-19 infection in patients with inborn errors of metabolism at a children’s hospital, reported a 26-year-old patient with MSUD who presented seven days after a positive COVID-19 test with encephalopathy and emesis after multiple days of poor appetite [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of COVID-19 infection in patients with MSUD have only been documented in two prior publications [ 6 , 7 ]. The first, an observational cohort study examining COVID-19 infection in patients with inborn errors of metabolism at a children’s hospital, reported a 26-year-old patient with MSUD who presented seven days after a positive COVID-19 test with encephalopathy and emesis after multiple days of poor appetite [ 6 ]. This patient’s leucine level peaked at 708 µmol/L, which was, for her, consistent with an acute metabolic crisis, and she was treated with a sick-day diet protocol and intravenous fluids, much like our patient.…”
Section: Discussionmentioning
confidence: 99%